2019
DOI: 10.1002/mmce.21944
|View full text |Cite
|
Sign up to set email alerts
|

Employing irises and septums to excite the centreline longitudinal slot antennas

Abstract: A suitable method is introduced to excite the centreline longitudinal slot antennas. For each slot, an iris and a rectangular septum are employed at the opposite sides of the slot such that they have offset from the waveguide centreline. It is shown that to form a high performance slotted array antenna consists of the centreline longitudinal antennas, employing antenna elements where each of them is excited only by an iris or a septum is not advisable. So, employing an iris and a septum all together is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It has been found that in the proposed dumbbell-shaped slot antennas, the septum length depends on the iris depth. To derive the appropriate septum length versus the iris depth, the procedure which has been offered in [49] was followed. Figure 2 shows the applicable septum length versus the iris depth.…”
Section: The Proposed Slot Antennasmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been found that in the proposed dumbbell-shaped slot antennas, the septum length depends on the iris depth. To derive the appropriate septum length versus the iris depth, the procedure which has been offered in [49] was followed. Figure 2 shows the applicable septum length versus the iris depth.…”
Section: The Proposed Slot Antennasmentioning
confidence: 99%
“…First, two standing wave slotted arrays consist of four waveguides and each waveguide contains four slots that have been designed and simulated. For the first array, all the antenna elements are centerline round-ended slots [49]. For the second array, the radiated elements are the proposed dumbbell-shaped slot antennas.…”
Section: Designing the Slotted Arrays Of The Dumbbell-shaped Slot Ant...mentioning
confidence: 99%
See 3 more Smart Citations